The Analysis of Halal Product Purchase Intention Using Theory Of Planned Behavior (TPB): An Application on Bakery Product Consumption - Aditami, Sofi; , Dr. Soepatini, SE., M.Si (2016)
This study is applying Theory of Planned Behavior as a theoretical framework with aim of extending prior research of examining halal bakery product purchasing behavior in Solo and Sukoharjo, Indonesia. Data are collected through questionnaire. The sample size of this research is 100 respondents, establishing validity through pearson-product moment. Non-probability convenience sampling is used for taking the sample. This study uses multiple regression analysis to identify the factors affecting halal bakery product purchasing behavior. The multiple regression analysis results indicate that all factors have positive and significant influence on halal bakery product purchasing intention. The results of the research showed: 1) There is a significant and positve impact between attitude and intention to purchase halal bakery products; 2) There is a significant and positve impact between subjective norm and intention to purchase halal bakery products; 3) There is a significant and positve impact between perceived behavioral control and intention to purchase halal bakery products. This study also confirms that Theory of Planned Behavior model is effectively predict halal bakery product purchase intention.